Digitalisasi dalam Manajemen Mutu Pendidikan: Penerapan Teknologi untuk Mendukung Proses Akreditasi Sekolah - Kunta, Ittaqillah Haitsuma; Muslim, Bukhori; Baharun, Hasan (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study aims to examine the application of technology in supporting the school accreditation process at MTs Zainul Hasan Genggong. This study employs a qualitative approach using a case study method to gain a deeper understanding of technology use in educational quality management, particularly in the accreditation process. Data was collected through in-depth interviews with the school principal, administrative staff, teachers, and information technology managers at the school, as well as through direct observation of the technology implementation. The results of the study indicate that the application of digital technology in the accreditation process has a positive impact on improving the efficiency and transparency of accreditation data processing. Cloud-based systems enable faster data collection and facilitate monitoring, but there are challenges related to staff mastery of technology and infrastructure limitations, particularly unstable internet connections. Additionally, although technology provides significant benefits, reliance on digital systems raises concerns in the event of technical disruptions, which require contingency plans. The conclusion of this study is that while the application of technology in accreditation has a positive impact, challenges related to training and infrastructure need to be addressed to achieve more optimal results. This study provides recommendations for other schools to adopt technology in the accreditation process and improve the quality of education through digitalization.